PENGARUH SIFAT MACHIAVELLIAN, LINGKUNGAN ETIKA DAN PERSONAL COSTTERHADAP INTENSI MELAKUKAN WHISTLEBLOWING (Studi Empiris Pada Bank BRI Provinsi Riau) - Giovanni Riand; Azwir Nasir; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose this study to examine the effect of machiavellianism, ethical environment and personal cost to whistleblowing intention. Based on purposive sampling method, this study used a sample of 86 respondents who work as internal auditors in BRI Bank Riau Province. This study used primary data with quetionary. Data were analyzed using multiple regression analysis with SPSS 17 processing. Variable in this study was whistleblowing intention as dependent variable, machiavellianism, ethical environment and personal cost as independent variable. The results showed that (1) machiavellianism effect on whistleblowing intention, with significant value 0,005 < 0,05, (2) Ethical environment effect on whistleblowing intention, with significant value 0,003 < 0,05, (3) personal cost effect on whistleblowing intention with significant value 0,005 < 0,05. The coefficient of determination in this study was 37%, where as 63% are influenced by variables that are not observed in this research model.Keywords : Machiavellianism, ethical environment, personal cost, whistleblowing